Social after pandemic distortion: towards thinking in planetary terms - Janković, Stefan (Sociološki pregled, 2020)
Along with climate change, the COVID-19 pandemic represents a specific planetary event, with surprising effects that require a rethinking of the social. The paper starts from the thesis that the pandemic essentially undermines modernity and the institutions of sovereignty, geopolitics and political economy due to their essential separation from non-human things. In the second part of the paper four propositions for a better understanding of planetary events are offered, including removing the difference of parts/wholes, non-relational thinking, rejecting the difference between global and local, and understanding collectives as constantly made in a continuum of humans and non-humas. Finally, the importance of speculation as the basis of planetary thinking is considered. There is a need to revise scientific practice and enhance its sensitivity to recognizing heterogeneous attachments of humans and non-humans in planetary settings.
Keywords: pandemic; planetary thinking; speculation